Sustainable Manufacturing and Green Processing Methods - Ali Khalfallah; Carlos Leitão (Machines)
Sustainable manufacturing and green processing methods have gained immense relevance over recent years due to pressing concerns over environmental degradation, resource scarcity, and industrial waste [...]